The h-Index: Understanding its predictors, significance, and criticism - Himel Mondal; Kishore Kumar Deepak; Manisha Gupta; Raman Kumar (Journal of Family Medicine and Primary Care)
The h-index is an author-level scientometric index used to gauge the significance of a researcher's work. The index is determined by taking the number of publications and the number of times these publications have been cited by others. Although it is widely used in academia, many authors find its calculation confusing. There are websites such as Google Scholar, Scopus, Web of Science (WOS), and Vidwan that provide the h-index of an author. As this metrics is frequently used by recruiting agency and grant approving authority to see the output of researchers, the authors need to know in-depth about it. In this article, we describe both the manual calculation method of the h-index and the details of websites that provide an automated calculation. We discuss the advantages and disadvantages of the h-index and the factors that determine the h-index of an author. Overall, this article serves as a comprehensive guide for novice authors seeking to understand the h-index and its significance in academia.